(3GdOdGFd Ydi eYGfi GdMOjK HGdTGgO hGdeKds - (3bGSe Hf KGHJ Hf MRe GdYhaj GdSQbSWj, CHh eMeO,J (B302 (3g` s
(3ChdgG (B:s
(3ef MOjK GdfYeGf Hf HTjQ QMeg Gdgd bGd (B: (3GSJYedfi YeQ Hf GdNWGH Ch YKeGf Hf YaGf , Ydi UObGJ SYO gRje , hge ZOQg hge ef bVGYI adeG bHVJ GdUQaI bSeJgG Hjf CgdgG s
(3BNQgG (B:s
(3hai MOjK dYHO Gdedc Hf eQhGf Cf QLdkG hUa dg XHjg UGOgG hThGgG bGd Ke cTWJ YfgG LdOgG cGdbHWjg GdHjVGA hCgd GdTGe jJNPhf GdaQfjI Ydi UfYI cjQ GdQLGLjf jNJHQhf ajg GdaQfjI ced cJGH GdOdGFd Ydi eYGfi GdMOjK HGdTGgO hGdeKd , JCdja CHj eMeO bs
(3HgG fXGe GdJYbjHIs
(3fSNI YJjbIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B174s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GddZIs